Modal split and travel times in the western NSB corridor in Oslo - Sandberg, Synnøve Lyssand; Næss, Petter (Proceedings from the Annual Transport Conference at Aalborg University, 1997)
How do investments in roads and public transport respectively, influence modal split and traveling times? The Norwegian Institute for Urban and Regional Research are in collaboration with Martin Mogridge Associates (London) undertaking a project aiming at answering this question. The discussion will be based on literature reviews and our own empirical research. Both cross sectional analyses and time sere analyses will be conducted in the empirical research. This paper presents empirical results from the first investigation in one of the two case corridors.